The Outcomes of Surgical Treatment of Cubital Tunnel Syndrome. - Virbickaitė, Eglė; Dedelytė, Emilija; Knystautas, Saulius; Gindriūnas, Simas; Braziulis, Kęstutis (Lietuvos chirurgija, 2023)
Background. Cubital tunnel syndrome is the second most commonly diagnosed compressive neuropathy of the upper extremity after carpal tunnel syndrome and the most common neuropathy of the ulnar nerve. Objective. To evaluate the results of surgical treatment of patients with cubital tunnel syndrome by performing an open decompression in situ. Methods. All subjects underwent a standard operation – open surgical opening of the elbow canal (decompression in situ). On the day of surgery, after 3 months, after 6 months, pain (verbal pain scale), hand and arm function (QuickDASH), complications are evaluated. Results. There were 44 patients, 16 (36%) female, 28 (64%) male. In 50% of the patients, electroneuromyography revealed a severe degree of ulnar nerve damage, in the rest – a moderate degree of damage. Hand function for women 3 months after surgery improved by 42.046 points (according to QuickDASH), while in men it was 15.454 points (p
Keywords: cubital tunnel syndrome neuropathy, surgical treatment, decompression in situ